The Implementation of Mimosa Pudica Root Extract for Anthracnose Disease On Red Chili to Increase Productivity - Eviyanti, Arifah (Proceeding International Conference on Science and Engineering, 2020)
Red chili is one of the important horticultural crops, both for domestic consumption and export commodity. Referring to the Indonesian agricultural information sistem (2016), the national consumption of red chili increases 2 % annually. Problems that occur in the cultivation of red chili plants in Indonesia is a disruption of pests and diseases. One of the diseases found in red chili plants is anthracnose disease caused by the fungi Colletotrichum sp marked spots. To control this disease, farmers usually use liquid chemical fungicide which is sprayed on red chili fruit continuously. A permanent use of the chemical fungicides can lead to pathogenic resistance, environmental damage and is harmful to consumers’ health. It means that we need to establish a sustainable agriculture of-which the developed products are not only renewable but also environment friendly. Therefore, in this research have a purpose to analyze the effect of Mimosa pudica root extract for anthracnose disease on red chili to increase farmers productivity. This research use method field study, which conducted on the chili land owned by farmer in Sukoharjo, Central Java. Which is done by giving Mimosa pudica root extract to the chili affected by anthracnose marked by spots, then compare after giving Mimosa pudica root extract. The study was conducted by spraying the extracts of Mimosa pudica root extract with concentration 0%, 25%, 50%, 75% and 100% (repeated 3 times) to the chilies. These results showed that the concentration of 25% was best result, proven by the results average spotting size before being given Mimosa pudica root extract is 2 cm then after being given Mimosa pudica root extract reduced to 1.3 cm. So the conclusion is Mimosa pudica root extract with concentration 25% can be an alternative vegetable fungicide to control anthracnose disease in red chili to increase productivity.